Gastrointestinal Stromal Tumour of Pelvic Wall: Report of a Case - Fazl QP; Mohammad Yousuf K; Nawab AK; Afak YS; Zubaida R; Rayees AM; Arif HS (Faculty of Medicine, UKM Medical Centre, 2015)
Gastrointestinal stromal tumors (GIST) because of its arity continues to be a curiosity for radiologists, surgeons and pathologist. These tumors are usually found in astrointestinal tract (GIT) but account for less than 1% of GIT tumors. A 35-year-old male presented to us with complaints of painful micturation which on radiologic evaluation revealed a large mass in relation to urinary bladder. The tru-cut biopsy reported a low grade soft tissue tumour. The said mass was excised on laparotomy and sent for histopathological examination which reported as high grade GIST or a pleomorphic sarcoma as possibilities. Immuno-histochemistry finally confirmed the diagnosis of a GIST with CD 34 positive and C-Kit negative status. Approximately, 95% of GIST tumors are C-Kit positive and hardly 5% are C-Kit negative. C-Kit negative status makes this case report more worth reporting.